Khaled Hosseini's women as modern archetypes: A study of obedient, resistant and empowered Afghan women - Imran, Muhammad; Ismail, Sayed M. (Frontiers in Sociology, 2022)
This article focuses on Khaled Hosseini's use of the analogy of women as obedient, resistant, and empowered as modern archetypes who learn of the gendered oppression that works through their bodies. Khaled Hosseini, through his writings, lends voice and offers moral encouragement to women by crafting resistant, rebellious, empowered, and strong female characters. With theoretical support from Johnson's Patriarchal Terrorism and Spivak's Can the subaltern speak, this article traces how Hosseini interrogates the patriarchal hierarchies that encompass women's identity in Afghanistan. Women's sufferings correlate with the country's overall circumstances, particularly during and after the war, on the terror regime. Therefore, women's endurance and Afghanistan's endurance amid hostile and oppressive circumstances become equally imperative for Hosseini's works. This article finds that Hosseini correlates Afghan women's issues like tradition and modernity, women and Islam, mother and daughter relationship, resistance and rebellion, and their quest for change and empowerment with the war on terror, foreign invasions, and the rule of the Taliban in Afghanistan.